High expression of antiviral proteins in mucosa from individuals exhibiting resistance to human immunodeficiency virus (2015)
Several soluble factors have been reported to have the capacity of inhibiting HIV replication at different steps of the virus life cycle, without eliminating infected cells and through enhancement of specific cellular mechanisms.